Community Energy Systems and the Law of Public Utilities. Volume Forty-seven. Vermont - Feurer, D. A.; Weaver, C. L. (Ross, Hardies, O'Keefe, Babcock and Parsons, Chicago, IL (USA), 1981)
A detailed description is presented of the laws and programs of the State of Vermont governing the regulation of public energy utilities, the siting of energy generating and transmission facilities, the municipal franchising of public energy utilities, and the prescription of rates to be charged by utilities including attendant problems of cost allocations, rate base and operating expense determinations, and rate of return allowances. These laws and programs are analyzed to identify impediments which they may present to the implementation of Integrated Community Energy Systems (ICES). This report is one of fifty-one separate volumes which describe such regulatory programs at the Federal level and in each state as background to the report entitled Community Energy Systems and the Law of Public Utilities - Volume One: An Overview. This report also contains a summary of a strategy described in Volume One - An Overview for overcoming these impediments by working within the existing regulatory framework and by making changes in the regulatory programs to enhance the likelihood of ICES implementation.